Analisis Penggunaan Model Pembelajaran Picture And Picture Pada Mata Pelajaran PKn Di MIN 2 Kota Medan - Annisaa Mawaddah; Sahkholid Nasution; Riris Nurkholidah Rambe (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
The research that has been carried out is entitled